2005 IEEE International Conference on Systems, Man and Cybernetics
DOI: 10.1109/icsmc.2005.1571506
|View full text |Cite
|
Sign up to set email alerts
|

A Joint Human-Automation Cognitive System to Support Rapid Decision-Making in Hostile Environments

Abstract: Honeywell has designed a joint humancomputer cognitive system to support rapid decision making demands of dismounted soldiers. In highly networked environments the sheer magnitude of communication amid multiple tasks could overwhelm individual soldiers. Key cognitive bottlenecks constrain information flow and the performance of decision-making, especially under stress. The adaptive decision-support system mitigates non-optimal human performance via automation when the system detects a breakdown in the human's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…In other recent studies involving ATCOs (Aricò et al, 2013, 2014, 2015b,c; Borghini et al, 2014; Di Flumeri et al, 2015; Toppi et al, 2016), it was demonstrated how it was possible to compute an EEG-based Workload Index able to significantly discriminate the workload demands of the ATM task, and to monitor them continuously by using frontal-parietal brain features. Other studies about the mental workload estimation by using neurophysiological indexes, have been proposed also in other operational contexts (Car drivers - Kohlmorgen et al, 2007; Borghini et al, 2012a; military domain - Dorneich et al, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…In other recent studies involving ATCOs (Aricò et al, 2013, 2014, 2015b,c; Borghini et al, 2014; Di Flumeri et al, 2015; Toppi et al, 2016), it was demonstrated how it was possible to compute an EEG-based Workload Index able to significantly discriminate the workload demands of the ATM task, and to monitor them continuously by using frontal-parietal brain features. Other studies about the mental workload estimation by using neurophysiological indexes, have been proposed also in other operational contexts (Car drivers - Kohlmorgen et al, 2007; Borghini et al, 2012a; military domain - Dorneich et al, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Looking at the papers that do fully articulate the proposed methods for expressing and constructing human actors' (level 2), all papers present a theory and an experiment. Dorneich et al [22] focus on the mental state of humans utilising neural networks, while Memon et al [28] are using natural language processing. Bollati et al [16] focus on handling changes supporting model transformations and Topcu [33] uses deliberative coherence theory to handle changes in goals.…”
Section: Rqmentioning
confidence: 99%
“…The U.S. Army conducted another related experiment, which focused on developing a mobile cognitive state classification test bed (Dorneich et al, 2007). This EEG-based system was not drythat is, participants had to wear standard laboratory leads with conducting gel, which were then connected to a laptop computer worn in a backpack.…”
Section: P R O V O C At I O N S Imentioning
confidence: 99%